APLIKASI LASER CO2 UNTUK PEMOTONGAN (CUTTING) MATERIAL MENGGUNAKAN MESIN CNC (CONTROL NUMERIC COMPUTER) - yenny toguan samarya (Saintia Fisika, 2013)
Laser cutting is a tecnology that uses a laser as cutter that is a cutting the material, works with led high power at a specific location laser cutting receive data directly from computers that could run on cutting automation CNC machine ( Control Numeric Computer ) . By designing the pattern cutting by using Autocad 2010 as CAD ( Computer Aided Desain ) and then converted to USBCNCV3 as CAM ( Computer Aided Manufacturing ) . Laser cutting process on the research using laser CO2 with the material to be cut is acrylic, plastic high voltage, and the plastic covers with size of 10 cm x 10 cm to be cut with a 10 cm diameter circle pattern by using power 3,5 watts. Laser cutting processs varied for blowing gas, materials, and the thickness of the material with the power and the focal point of the laser CO2 anyway. Keywords : Laser cutting, laser CO2, CAD, CAM